Provision of low‐iron micronutrient powders on alternate days is associated with lower prevalence of anaemia, stunting, and improved motor milestone acquisition in the first year of life: A retrospective cohort study in rural Ethiopia. Issue 3 (15th March 2019) - Geletu, Ashenafi; Lelisa, Azeb; Baye, Kaleab
Abstract: Inappropriate complementary feeding contributes to growth faltering, anaemia, and cognitive impairments. Limited programmatic evidence exists on the effectiveness of low‐iron micronutrient powders (MNPs) on anaemia and motor development when provided every other day in the first year of life. This study used an existing demonstration project to evaluate associations between exposure of low‐iron MNPs, anaemia, and motor development of infants in Southern Ethiopia. Using a retrospective cohort design, 200 infants aged 9 to 12 months (98 MNP exposed; 102 unexposed) were recruited, and data on socio‐economic characteristics, anthropometric measures, dietary diversity scores (DDS), haemoglobin concentrations, and motor development acquisition were collected, and MNP exposed and unexposed groups were compared. Logistic regressions were run to identify predictors of acquisition of motor development milestones. Sociodemographic characteristics and dietary diversity scores were similar between MNP exposed and unexposed groups. Provision of low‐iron (6 mg) MNP every other day, for 3 months, was associated with reduced risk of anaemia and stunting and increased achievement of motor development. After adjusting for age, infants exposed to MNPs had a higher likelihood of standing alone (AOR = 3.1; 95% CI [1.53, 6.46]) and walking alone (4.9; 95% CI [2.12, 11.37]) than unexposed ones. Exposure to MNPs, DDS, stunting, and mothers education were associated with acquisition of motor development milestones. Provision of low‐iron dose MNPs on alternate days is associated with lower prevalence of anaemia, stunting, and increased motor development achievements. Integrating routine monitoring of motor development milestones with growth monitoring and anaemia screening can inform nutrition interventions to support optimal brain development.